Pengembangan Metode Pembelajaran CIRCOS untuk Meningkatkan Prestasi Belajar Siswa - Khusnul Khotimah; Dian Kusuma Wardani (Universitas KH. A. Wahab Hasbullah, 2020)
Education is one of the supporting factors in improving the quality of human resources. Therefore the concept of an education should no longer be teacher-centered, but student-centered. The change in concept starts from several aspects, one of which is through the learning method. Some learning methods that center on student activity are the Circuit Learning and Complete Sentence methods. Through these two methods, students are expected to be more active and get satisfying results. Therefore, in this study the two methods were developed into a new method, the CIRCOS method to determine the application of the learning method and its effect on increasing student achievement. This research method uses Research and Development, and uses the Borg and Gall model. Data collection techniques in this study through observation, interviews, questionnaires, and documentation. In the research instrument using questionnaires and tests. Based on the results of research and development, it can be concluded that the CIRCOS learning method has several weaknesses, strengths, and things that need to be added. And the CIRCOS method can improve student achievement.